Educational policies, territories and actors strategies - Sebastião, João; Campos, J.; Merlini, S.; Chambino, M. (Italian Journal of Sociology of Education, 2013)
The purpose of this paper is to analyse how educational policies about school violence are reinterpreted and implemented at school level and if this process contributes to a more pluralistic and democratic school. A research carried out in 3 clusters of schools showed that the diversity of understandings and strategies to face school violence, higher within the territories than between them, was associated to the school board's agendas and the legitimacy of the different actors to interpret and act within the national policies framework. There was a high consistency between violence management strategies and the ways schools faced social and cultural diversity. Those who favour more inclusive strategies to deal with violence tend to provide higher educational opportunities in schools, inversely, those who favour repressive strategies are more likely to support educational and social selective strategies, with less educational offer; less participation of teachers, students and parents in violence regulation.